The motivation trap leadership strategies to achieve sustained success - John Hittler (Austin, Texas Greenleaf Book Group Press, 2018)
CEOs and team leaders from Fortune 500 companies and venture-backed start-ups often complain that they have trouble keeping their teams motivated. But what if it's actually not the job of the leaders to motivate their teams? What if team members were responsible for motivating themselves and for bringing their own professional, positive, helpful, best selves to work each day? What might change in companies if teams lived up to this expectation? In The Motivation Trap, John Hittler draws on the wisdom he has acquired from years of coaching individuals, teams, and organizations and proposes a more effective way to lead. He unwraps the energetic underpinnings of motivation, explains why it holds big limitations, and points out where and when to employ it as an effective tool in coaching management teams. He walks readers through additional tools and suggests how and when to use them to create high-achieving teams who find enjoyment in their work and are ready to take initiative and work more autonomously. His simple, easy-to-use tools will bring team members together so they can accomplish highly leveraged success. With the wisdom he provides in The Motivation Trap, Hittler helps leaders produce great results for their team members, themselves, and their organizations.
Keywords: Employee motivation